2001
DOI: 10.1111/j.8755-8920.2001.450403.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐Specific Glycoproteins Function as Immunomodulators by Inducing Secretion of IL‐10, IL‐6 and TGF‐β1 by Human Monocytes

Abstract: PSG1, PSG6, PSG6N, and PSG11 induce dose-dependent secretion of anti-inflammatory cytokines by human monocytes. Human and murine PSGs exhibit cross-species activity. Our results are consistent with a role for PSGs in modulation of the innate immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 33 publications
12
118
0
1
Order By: Relevance
“…36 One possible mechanism of IL-6 in preventing miscarriage is modulation of the quality of the Th2 response by increasing the proportion of blocking asymmetric antibodies during implantation and placental vascularization. 62 Although the sensitivity and specificity of the cytokines/receptors in our study are not accurate enough for treatment decisions, a combination of cytokines together with other biomarkers in the future may prove to be useful clinically. Previous studies have shown that TNFreceptors are useful in first-trimester screening of women who are at subsequent risk of preeclampsia.…”
Section: Wwwajogorgmentioning
confidence: 80%
See 1 more Smart Citation
“…36 One possible mechanism of IL-6 in preventing miscarriage is modulation of the quality of the Th2 response by increasing the proportion of blocking asymmetric antibodies during implantation and placental vascularization. 62 Although the sensitivity and specificity of the cytokines/receptors in our study are not accurate enough for treatment decisions, a combination of cytokines together with other biomarkers in the future may prove to be useful clinically. Previous studies have shown that TNFreceptors are useful in first-trimester screening of women who are at subsequent risk of preeclampsia.…”
Section: Wwwajogorgmentioning
confidence: 80%
“…Recently, it has been demonstrated that IL-6 is involved in the promotion of Th2 differentiation and the inhibition of Th1 polarization. 62 During the first trimes- Receiver operator characteristics (ROC ) curves for each cytokine and receptor Tumor necrosis factor (TNF )-R2 was shown to be the biomarker that best predicts miscarriage, with an area under the curve of 0.65 (95% confidence interval, 0.47-0.75). A cutoff level of 2202 pg/mL of TNF-R2 gave a sensitivity of 63%, a specificity of 62%, and a positive predictive value of 44% for the prediction of miscarriage.…”
Section: Commentmentioning
confidence: 99%
“…34 In addition, genes involved in renal system processes, neuron development, and cell proliferation (natriuretic peptide precursor b, endothelin1 and 2, bone morphogenic protein, fibroblast growth factor 8) were also down regulated by Fe 2 O 3 but not by MCM-41. Defense response and stress associated genes pregnancy specific beta1 glycoproteins (PSG1 and PSG2) 35 were significantly induced by Fe 2 O 3 while only PSG1 was induced by MCM-41.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this glycoprotein is able to suppress the accessory cell-dependent T cell proliferative response, whereas it does not alter the ability of T cells to respond to accessory cell-independent stimuli [15]. Furthermore, murine PSG17 and PSG18 mimic the biological effects of human PSG inducing IL-10, IL-6 and TGF-g expression in human Mo [16], and human PSG1, PSG6 and PSG11 induce the secretion of anti-inflammatory cytokines by human and murine Mo [17]. These findings prompted us to find out whether PSG1a, when released into circulation, may have a role in shifting the T cell immune response to Th2 pathway through the induction of alternative activation of Mo.…”
Section: Introductionmentioning
confidence: 99%